Pat Shipman, Our Oldest Companions: The Story of the First Dogs - Krone, Adrienne (Journal for the study of religion, nature and culture, 2023)
Pat Shipman, Our Oldest Companions: The Story of the First Dogs (Cambridge: The Belknap Press of Harvard University Press, 2021), 247 pp., $25.95 (hbk), ISBN: 9780674971936.